الإصلاحات الجبائية في الجزائر- مرجع نوعية الخدمة دعامة لرفع الثقافة الجبائية - تابتي خديجة (جامعة الوادي University of Eloued, 2024)
تبنت الإدارة الجبائية جملة من الإصلاحات مست عدة مستويات سواء من ناحية الإجراءات و التدابير الجبائية، الأساليب الحديثة في التسيير و إدخال التكنولوجيات ،و عصرنة الهياكل الإدارية بغية تقديم خدمة أفضل للمكلفين بالضريبة بهدف رفع الوعي الجبائي لديهم الذي يرتبط ارتباط وثيق بجودة الخدمة المقدمة لهم. و من خلال هذه الدراسة نهدف إلى تسليط الضوء على الأساليب الحديثة المستعملة على مستوى هياكل الاستقبال التابعة للهياكل الإدارية الحديثة، و من أهمها مرجع نوعية الخدمة و ذلك باستخدام المنهج الوصفي التحليلي للإحاطة بمختلف جوانب النظرية للدارسة و تحليل البيانات و الإحصائيات المتحصل عليها، و قد توصلت نتائج الدراسة إلى أن الاعتماد على هذا الأسلوب رفع من جودة الاستقبال و الإعلام و توفير المعلومات و المستجدات و سهولة الوصول إليها من طرف دافعي الضرائب و منه عزز ثقتهم و ثقافتهم الجبائية، و كسر الحواجز القائمة ما بين الإدارة و النسيج الجبائي. The tax administration adopted a set of reforms that touched several levels, both in terms of tax procedures and measures, modern methods of management, the introduction of technologies, and the modernization of administrative structures in order to provide better service to taxpayers with the aim of raising their tax awareness, which is closely linked to the quality of service provided to them. Through this study, we aim to shed light on the modern methods used at the level of reception structures affiliated with modern administrative structures, the most important of which is the quality of service reference, by using the descriptive and analytical approach to cover the various theoretical aspects of the study and analyze the data and statistics obtained. The results of the study concluded that relying on This method increased the quality of reception and information, the provision of information and developments, and the ease of access to them by taxpayers, thereby strengthening their confidence and tax culture, and breaking down the existing barriers between administration and the tax fabric.
Fiscal reform In Algeria-Service Quality Reference Support for raising tax culture
Keywords: الاصلاحات الجبائية; الثقافة الجبائية; الإدارة الجبائية; تقييم الأداء: Tax reforms; Service Quality Reference; fiscal awarness; fiscal administration; performance evaluation